2008
DOI: 10.1128/aem.01442-08
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Temperature on the Die-Off Rate for Cryptosporidium parvum Oocysts in Water, Soils, and Feces

Abstract: 2The zoonotic protozoan parasite Cryptosporidium parvum poses a significant risk to public health and has become a global concern for water resource management (10). In order to identify the risk of potential contamination, knowledge about the survival of Cryptosporidium oocysts in the environment is required. Cryptosporidium oocysts can retain infectivity for months and resist environmental stresses more readily than many other pathogens because of a hard protective wall (10,15,41). As a result, the character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 47 publications
3
48
0
Order By: Relevance
“…Low temperatures above freezing extend oocyst viability and infectivity for very long times (12,18,19,20,35). Environmental temperature is a major factor controlling oocyst survival (23,24,32). While there have been many studies documenting the significance of temperature for oocyst survival and the influence of temperature on stored energy reserve utilization has been recognized (see references 10 and 32 for reviews), the effects of temperature on the key oocyst wall structures and macromolecules have not been well investigated.…”
mentioning
confidence: 99%
“…Low temperatures above freezing extend oocyst viability and infectivity for very long times (12,18,19,20,35). Environmental temperature is a major factor controlling oocyst survival (23,24,32). While there have been many studies documenting the significance of temperature for oocyst survival and the influence of temperature on stored energy reserve utilization has been recognized (see references 10 and 32 for reviews), the effects of temperature on the key oocyst wall structures and macromolecules have not been well investigated.…”
mentioning
confidence: 99%
“…5 During the tests, the temperature in the interior of the reactor was registered every 1 hour, because this temperature is also a critical factor to determine the survival of the infective forms of C. parvum in the environment. 32 Thus, the maximum temperatures were reached in the most turbid water samples (30 NTU), reaching as high as 57 C during the last 2 hours of the assay. In addition, in previous SODIS studies also carried out under field conditions, the phenomenon of spontaneous excystation was observed.…”
Section: Discussionmentioning
confidence: 90%
“…In a recent review of the effect of temperature on the die-off rate for C. parvum oocysts in water, soil, and feces, 28 the authors concluded that temperature may be the most lethal factor for Cryptosporidium in the environment. The studies included in this review were classified into those in which freezing conditions were tested, others in which temperature between 0°C and 37°C were assayed, and those in which temperatures greater than 45°C were used, with exposure times between one and several minutes for high temperatures 29 and weeks and even months for freezing and environmental temperatures.…”
Section: Discussionmentioning
confidence: 99%